Abnormal Serotonin Levels During Perinatal Development Lead to Behavioral Deficits in Adulthood - Shah, Relish; Courtiol, Emmanuelle; Castellanos, Francisco X.; Teixeira, Catia M. (Frontiers in Behavioral Neuroscience, 2018)
Serotonin (5-HT) is one of the best-studied modulatory neurotransmitters with ubiquitous presynaptic release and postsynaptic reception. 5-HT has been implicated in a wide variety of brain functions, ranging from autonomic regulation, sensory perception, feeding and motor function to emotional regulation and cognition. The role of this neuromodulator in neuropsychiatric diseases is unquestionable with important neuropsychiatric medications, e.g., most antidepressants, targeting this system. Importantly, 5-HT modulates neurodevelopment and changes in its levels during development can have life-long consequences. In this mini-review, we highlight that exposure to both low and high serotonin levels during the perinatal period can lead to behavioral deficits in adulthood. We focus on three exogenous factors that can change 5-HT levels during the critical perinatal period: dietary tryptophan depletion, exposure to serotonin-selective-reuptake-inhibitors (SSRIs) and poor early life care. We discuss the effects of each of these on behavioral deficits in adulthood.